1991
DOI: 10.1128/jcm.29.12.2704-2709.1991
|View full text |Cite
|
Sign up to set email alerts
|

Development of verotoxin 2- and verotoxin 2 variant (VT2v)-specific oligonucleotide probes on the basis of the nucleotide sequence of the B cistron of VT2v from Escherichia coli E32511 and B2F1

Abstract: We and others have noted that there are serological differences between verotoxin 2 (VT2) (also known as Shiga-like toxin II) produced by Escherichia coli C600(933W) and the VT2 variant (VT2v) produced by strain E32511. Recent reports have described nucleotide sequence differences between the VT2v B subunit cistron of E32511 and B2F1 and that of VT2. We have confirmed the sequence differences and have used them to design oligonucleotide probes which differentiate the B subunit cistron of VT2v from that of VT2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 26 publications
(49 reference statements)
3
31
0
Order By: Relevance
“…Regarding the virulence traits obtained for 34 strains of STEC isolated from naturally-contaminated samples, the data suggest that some variants occurred, which is in agreement with the increasing number of variants recently described in the literature (Gyles et al 1988;Weinstein et al 1988 9 ; Gannon et al 1990;Ito et al 1990;Hii et al 1991;Paton et al 1992Paton et al , 1993cLin et al 1993b, b;Kim et al 1997;Pierard et al 1998 10 ). These variants were usually described as Stx2 strains of STEC, while variants derived from Stx1 strains are rarely reported (Paton et al 1993a(Paton et al , 1995a.…”
Section: Discussionsupporting
confidence: 86%
“…Regarding the virulence traits obtained for 34 strains of STEC isolated from naturally-contaminated samples, the data suggest that some variants occurred, which is in agreement with the increasing number of variants recently described in the literature (Gyles et al 1988;Weinstein et al 1988 9 ; Gannon et al 1990;Ito et al 1990;Hii et al 1991;Paton et al 1992Paton et al , 1993cLin et al 1993b, b;Kim et al 1997;Pierard et al 1998 10 ). These variants were usually described as Stx2 strains of STEC, while variants derived from Stx1 strains are rarely reported (Paton et al 1993a(Paton et al , 1995a.…”
Section: Discussionsupporting
confidence: 86%
“…Eight of them possessed stx1 and stx2 genes, and one possessed stx2 and G1 genes. Similar differences in Stx2 variant distribution were also reported by Thomas et al [23], Tayler et al [24], and Hii et al [15]. It is interesting that the oldest strain in our collection, isolated in 1986, possessed stx2 and G1 genes, and that the G1 gene was present in most of the prefectures in Japan.…”
Section: Discussionsupporting
confidence: 89%
“…However, variable and con£icting results have been reported with regard to the prevalence of Stx2 variants. While Tyler et al reported that all seven E. coli O157:H7 isolates contained stx2vha [14], Hii et al did not ¢nd the Stx2 variant pheno^genotype in any of their 23 E. coli O157:H7 strains [15]. Ru « ssmann et al reported that 17 of 38 strains from HUS patients possessed stx2c [16], and Nishikawa et al reported that 61 of 169 E. coli O157 strains isolated in Japan possessed stx2vha [17].…”
Section: Introductionmentioning
confidence: 99%
“…These SLT-II group members include SLT-Ilvha (VT2vha), SLT-Ilvhb (VT2vhb), and SLT-IIc, all of which are nearly 97% homologous to SLT-1I at the deduced amino acid sequence level (14,45). Other SLT-II-related toxins have been described (8,12,21,30,37,44,54,59), but many of these toxins were detected by PCR analysis and only a few have been isolated and sequenced.…”
Section: Infection With Enterohemorrhagic Escherichia Coli (Ehec)mentioning
confidence: 99%